Sensing Home: A Thematic Analysis of Psychoanalytic Texts - Isaac, Hayden Mark (Auckland University of Technology, 2020)
How we sense our homes has an impact on how we interact with the environments we live in and how we view ourselves. Yet, the author found little research in the psychoanalytic tradition, object relations, that explores the intrapsychic faculty that we sense home through. Thus, this research project employs a research methodology that is similar to Crotty’s (1998) description of social constructionism, and the research method that Braun, Clarke, and Hayfield (2015) calls descriptive thematic analysis, to interpret how 11 psychoanalytic articles portray the development of this sense faculty. In doing so, this project begins to outlay a landscape of this phenomenon, constructing five themes in the literature that could aid future research and clinical explorations; themes that portray how the phenomena we call home, symbolic processes, psychic integration and individuation, as well as the wake of trauma impacts the way we sense the places and relationships that we inhabit. As a result, these themes have several implications for psychotherapeutic practice, clinical training, the research of psychotherapy, and other research areas.
Keywords: Home; Psychoanalysis; Psychotherapy; Object Relations; Thematic Analysis; Intrapsychic Sense of Home; Sense of Home; Sense of Homelessness; Human Development